Proteomic analyses of Elaeis guineensis Jacq.(African Oil Palm) basal stem rot disease related to Ganoderma boninense / Leona Daniela Jeffery Daim - Leona Daniela, Jeffery Daim (2017)
Ganoderma boninese is a basidiomycete fungal pathogen. It mainly attacks the roots of oil palms which will lead to the basal stem rot (BSR) disease. The oil palm industry suffers yearly crop losses that are attributed to the spread of this disease. To obtain a clearer picture of expression profiles of the ever changing global protein network in ganoderma infected plants, a gel-based proteomics approach was conducted using leaf tissues sampled from young palms. Leaf tissues were used for experimental analysis mainly because they were easier to sample than root tissues. Even though the mechanism of infection of this disease is through the root systems, early detection of the disease by source of leaves is an added advantage. This is because tissues could be sampled without wounding the roots, thus rendering them exposed to possible disease infection. Differential analysis of the leaf proteome revealed 116 protein spots that changed in abundance. Identification of these spots revealed proteins that changed in carbohydrate metabolism, cellular component, energy production, fatty acid biosynthesis, immunity and defence, nitrogen metabolism, protein metabolism, stress response, transport, and photosynthesis. Some of these changes were then validated using Western blots. In-depth literature reviews showed that proteins involved in immunity and defence, specifically peroxiredoxin, detoxify reactive oxygen species that are harmful to the plants: Proteinprotein interaction studies showed that peroxiredoxins interacted with a disease resistance protein. These results suggest the possibility of further investigation into disease resistance proteins in host-pathogen interactions. The results obtained from the proteomic analyses of leaf tissues from inoculated oil palms could be used as a tool in early detection of the BSR disease. Additional validation and further investigations into these proteins could improve our biological understanding towards this disease.